A personal space in the Web. Bases, processes and evaluation of a collaborative digital design experience for significant learning. (September 2017) - Tosello, María Elena; Bredanini, María Georgina
We live constantly networked, performing multiple activities in virtual spaces which are intertwined with physical space, shaping an augmented and symbiotic chronotope. Considering that personal space is an area surrounding individuals that provides a framework for developing activities wouldn't it be necessary to count on a virtual personal space? This article presents the bases, processes, and results of a didactic experience which purpose was to imagine and design a personal space in the Web, representing its properties and characteristics through a transmedia narrative unfolded through diverse languages and media. Three cases are presented, selected because they propose different strategies to approach the problem. In order to perform a comparative analysis of the results, the categories were defined based on the triadic structure of Peirce's Theory of Signs, which in turn were divided into sub-categories that incorporate the Principles of Design and Evaluation of Interface-Spaces.